Smart Phones and Personal Listening Devices - Tinnitus & Hearing Impairment in Adolescent and Young Adult Earphone Users - Anwar, Khurshid; Yar Mohammad, Adnan; Khan, Saeed (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To determine the frequency of tinnitus & hearing impairment in adolescent and young adult earphone users with smartphones and other personal listening devices. METHODOLOGY This prospective & descriptive study involving children with glue ears was conducted in the ENT Department of Medical Teaching Institute, Hayatabad Medical Complex, Peshawar, from Jan 1, 2022, to Sep 30, 2022. Personal listening device (PLD) users aged 12-25 years with complaints of tinnitus and hearing impairment were examined. Conductive hearing loss was excluded by audiological testing. The frequency of resultant hearing loss and tinnitus was calculated. The information obtained was analyzed using SPSS v 26.0 for windows. A Chi square test was performed to determine the significance of tinnitus & hearing impairment in earphones and other PLD users. RESULTS A total of 163 patients were included in the study. The patient’s age range was 12-25 years, with a mean age of 18.03 years and a standard deviation of ± 3.575. There were 117 males and 46 females. The male: female ratio was of 2.54:1.Tinnitus was present in 73% and Hearing impairment in 54.4% of the patients. The chi-square test and p-values determined showed that both tinnitus and hearing loss occurred in many patients using personal listening devices. CONCLUSION Tinnitus and hearing impairment occurs in a significant number of those who use personal listening devices. Their inappropriate use can lead to auditory system damage. It is recommended that PLD users undergo periodic audiological testing to detect early hearing loss and tinnitus to minimize damage to the ear.